USAGE OF PEPTIDE ANTIGENS FOR ANTIBODY-BASED BoNT DETECTION SYSTEM - (:unkn) unknown (My University, 2021)
Objective: In the current study, we aimed to elicit a BoNT-specific immune response via using peptides designed by using bioinformatics toolsinstead of using intact native BoNT A toxin itself and to demonstrate the usage of these anti-peptide antibodies in a toxin detection system.Methods: Synthetic epitopic regions specific to LC, HN and HC regions of BoNT A were selected as antigen using B cell “Epitope PredictionTools” form IEDB and shown to be on the surface of BoNT A with a software (Discovery Studio 4.0). Selected peptides were used in miceimmunizations and the interaction between developed anti-peptide antibodies and the native intact BoNT A was examined.Results: The detection of native intact BoNT A at picogram levels per milliliter was performed with anti-peptide antibodies developed againstthree different peptides (P1, P2, and P3) in mice.Conclusion: The current study shows that synthetic peptides are at least as effective as the native toxin or the toxoid itself for raising high-affinityantibodies against toxins. In addition, considering the need for a quick diagnosis of botulism and, already used test systems in which manyexperimental animals are sacrificed, these results demonstrate the necessity of synthetic peptide immunogens usage to reduce both the number ofanimals and the amount of toxin usage.

Amaç: Bu çalışmada, doğal yapılı BoNT A toksininin kendisi yerine biyoinformatik araçlar kullanılarak tasarlanan peptitleri kullanarak BoNT'ye_x000D_ özgü bir bağışıklık tepkisi ortaya çıkarmayı ve bu anti-peptit antikorlarının bir toksin tespit sisteminde kullanımını göstermeyi amaçladık._x000D_ Yöntem: BoNT A'nın LC, HN ve HC bölgelerine özgü sentetik epitopik bölgeler, IEDB'den B hücresi "Epitop Tahmin Araçları" kullanılarak_x000D_ antijen olarak seçildi ve bir yazılımla (Discovery Studio 4.0) BoNT A yüzeyinde olduğu gösterildi. Seçilen peptidler, fare bağışıklamalarında_x000D_ kullanıldı ve geliştirilen anti-peptid antikorları ile doğal yapılı BoNT A arasındaki ilişki incelendi._x000D_ Bulgular: Farelerde üç farklı peptide (P1, P2 ve P3) karşı geliştirilen anti-peptid antikorları ile mililitrede pikogram seviyelerinde doğal yapılı_x000D_ BoNT A'nın saptanması gerçekleştirildi._x000D_ Sonuç: Bu çalışma, sentetik peptitlerin, toksinlere karşı yüksek afiniteli antikorları geliştirmek için en az doğal toksin veya toksoidin kendisi kadar_x000D_ etkili olduğunu göstermektedir. Ayrıca botulizmin hızlı teşhisine duyulan ihtiyaç ve halihazırda kullanılan test sistemlerinde çok sayıda deney_x000D_ hayvanının kurban edildiği göz önüne alındığında, bu sonuçlar hem hayvan sayısını hem de toksin kullanım miktarını azaltmak için sentetik peptit_x000D_ immünojenlerinin kullanılmasının gerekliliğini ortaya koymaktadır.
ANTİKOR BAZLI BoNT TESPİT SİSTEMİ İÇİN PEPTİT ANTİJENLERİN KULLANIMI